Compassionate statistics : applied quantitative analysis for social services : with exercises and instructions in SPSS /: applied quantitative analysis for social services : with exercises and instructions in SPSS. ([2012?]) - Faherty, Vincent E (Vincent Edward), 1939-
No abstract available